Corporate Governance Quality's Moderating Effect on Profitability, ESG Disclosure, and Green Innovation - Maristiana Ayu. Ms; Ani Pujiati; Ade Sandra Dewi (Penerbit Goodwood, 2026)
Purpose: The impact of ESG disclosure and profitability on green innovation is examined in this study, with the moderating role of corporate governance quality assessed among publicly listed companies in Indonesia.Research Methodology: Quantitative approach was employed, and panel data from 19, the analysis was conducted on the Sri?Kehati Index over the 2020–2024 period, employing moderated panel data regression techniques.Results: The study found that ESG disclosure and profitability positively influence green innovation, with this relationship being reinforced by the quality of corporate governance. Consequently, the ability of ESG practices and financial performance to foster green innovation was shown to rely on robust governance mechanisms.Conclusions: The impact of ESG disclosure and profitability on green innovation was found to be moderated and enhanced by the quality of corporate governance.Limitations: Several limitations were identified, including the limited number of samples, the relatively short observation period, and the use of index-based disclosure measurements, which might not entirely reflect the actual effectiveness of sustainability practices.Contributions: This study contributes to the literature by showing that the impact of ESG disclosure and profitability on green innovation is strengthened by corporate governance quality. The application of Resource-Based View, Legitimacy, and Agency Theories is extended to emerging markets, and practical implications are provided for investors and policymakers.